A method for improving the selectivity of hydrogenation reaction to generate intermediate products
By using silica and copper-based catalysts supported by surface oxygen-containing defective substances, the problem of high-cost precious metal catalysts in the prior art is solved, and the selectivity of ethylene and cost savings in the acetylene hydrogenation reaction are improved.
Patent Information
- Application Number
- CN202310134365.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-20
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2043-02-20
AI Technical Summary
The palladium, gold or platinum catalysts used in the catalytic hydrogenation reaction of existing acetylene have high costs and are difficult to produce on a large scale. The acetylene content affects product quality and economic benefits in ethylene production.
Using a copper-based catalyst with silica and surface oxygen-containing defective substances as support, it supports Cu atom clusters and/or Cu single atoms, and is prepared by ammonia distillation method to control the load and size of copper species to achieve low temperature migration to form Cu atoms. Cluster, avoid reunion.
The selectivity of ethylene in the acetylene hydrogenation reaction is improved, the catalyst production cost and product separation energy consumption are reduced, the catalytic activity comparable to that of noble metal catalysts is achieved, and it is suitable for large-scale production.
Smart Images

Figure CN116003203B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of copper-based catalysts, and in particular relates to a method for improving the selectivity of hydrogenation reactions to generate intermediate products. Background Art
[0002] Ethylene is an important raw material for the global chemical industry, and its output is an important criterion for measuring the level of petrochemical industry. The industrial production of ethylene is mainly obtained by high-temperature catalytic cracking of liquid naphtha, and about 1% of acetylene gas will be produced in the cracked product. The acetylene content in the polymerization-grade ethylene used in the production of ethylene glycol in industry is required to be less than 5ppm, so the presence of excessive acetylene will not only affect the quality of ethylene products, but also reduce the economic benefits of subsequent production processes.
[0003] When the acetylene content in the ethylene production process is low and the production scale is large, the method of using acetylene catalytic hydrogenation to generate ethylene for deacetylation has considerable prospects in terms of process operation and economic cost. The catalyst currently used in the acetylene catalytic hydrogenation reaction is a supported metal catalyst containing palladium, gold or platinum, which is costly and not conducive to large-scale production. Therefore, the development of non-precious metal catalysts with high selective hydrogenation performance is conducive to the further development of the deacetylation process.
[0004] The present invention aims to solve the above-mentioned problems. Summary of the invention
[0005] The first aspect of the present invention provides a method for improving the selectivity of hydrogenation reaction to generate intermediate products. The selective hydrogenation reaction is a reaction of selectively hydrogenating acetylene to generate ethylene. The catalyst used is a copper-based catalyst loaded with Cu atomic clusters and / or Cu single atoms on a mixed carrier. The copper-based catalyst includes a carrier and an active component. The carrier is silicon dioxide and a substance containing oxygen defects on the surface. The mass ratio of silicon dioxide to the substance containing oxygen defects on the surface is 1:(3.6-7.2); the active component is a copper species, and the copper species is a Cu atomic cluster composed of a Cu single atom and / or several Cu atoms. The size of the Cu atomic cluster is less than 0.8 nm. Based on the total mass of the copper-based catalyst, the loading amount of the copper species is 5%-7%.
[0006] Preferably, acetylene is mixed with hydrogen and then introduced into the reactor, and the mass space velocity of acetylene is 800 to 1300 h -1 , the ratio of acetylene, hydrogen and nitrogen is 1:10:89, the reaction temperature in the reactor is 80-240°C, and the reaction pressure is normal pressure-0.1MPa. In this application, the selectivity of the product ethylene is greater than 90%, and even as high as 95%.
[0007] Preferably, the substance containing oxygen defects on the surface is a metal oxide containing oxygen defects on the surface, and the metal oxide containing oxygen defects on the surface is selected from cerium oxide, zinc oxide, zirconium oxide, titanium oxide or manganese oxide.
[0008] Preferably, the silicon dioxide has a layered structure, and the particle size of the substance containing oxygen defects on the surface is 4.0 nm to 20.0 nm.
[0009] Preferably, the average valence of copper in the copper species is 0-1.
[0010] Preferably, the number of Cu atoms in the Cu atom cluster is less than 100, preferably less than 60, more preferably less than 30, still more preferably less than 15, even more preferably less than 6, and most preferably less than 3.
[0011] The method for preparing a copper-based catalyst using a mixed carrier to support Cu atomic clusters or Cu single atoms comprises the following steps:
[0012] (1) providing a material of silica-supported copper oxide nanoparticles as a first raw material, wherein the particle size of the copper oxide nanoparticles is less than 4 nm;
[0013] (2) providing a substance containing surface oxygen defects as a second raw material;
[0014] (3) mixing the second raw material with the first raw material, and performing the first stage and the second stage treatment after the mixing; or,
[0015] The first raw material is first subjected to a first stage reduction treatment, and then mixed with the second raw material, and then subjected to a second stage treatment after mixing;
[0016] The copper-based catalyst is obtained after the first and second stage treatments. The first stage reduction treatment reduces the copper oxide nanoparticles supported on the silicon dioxide to copper nanoparticles, and the second stage treatment causes the copper nanoparticles to migrate to the surface oxygen-deficient substances to form Cu single atoms or Cu atom clusters, thereby obtaining the copper-based catalyst.
[0017] Preferably, the mass percentage of copper in the silica-loaded copper oxide nanoparticles in step (1) is 5% to 50%.
[0018] Preferably, the method for preparing the first raw material of silicon dioxide-loaded copper oxide nanoparticles in step (1) comprises the following steps:
[0019] (11) dissolving copper nitrate trihydrate in water, then adding ammonia water, stirring and mixing to obtain a first mixed solution;
[0020] (12) adding silica sol dropwise to the first mixed solution, stirring, and then distilling off ammonia components in the first mixed solution to obtain a second mixed solution;
[0021] (13) Filtering the second mixed solution obtained in step (12), collecting the filter cake, washing it, and calcining it in an air atmosphere to obtain a material of silica-loaded copper oxide nanoparticles.
[0022] Preferably, the concentration of aqueous ammonia in step (11) is 20% to 28%; the volume ratio of aqueous ammonia to water is 1:1.12 to 1:2.31; the distillation temperature in step (12) is 60°C to 90°C, and the pH of the solution after distilling away the ammonia component in the first mixed solution is 6.5 to 8.5.
[0023] The amount of copper nitrate trihydrate and silica sol added in step (11) is designed according to the mass fraction of copper in the silica-loaded copper oxide nanoparticles finally obtained, and the mass fraction of copper in the silica-loaded copper oxide nanoparticles is 5% to 50%.
[0024] The specific surface area of the first raw material prepared by the above method is 400-600m 2 / g, average pore volume is 0.3~1.1cm 3 / g, an average pore diameter of 3.0-10.0 nm, and a particle size of the copper oxide nanoparticles less than 4 nm.
[0025] Preferably, in step (3), the mass ratio of the first raw material to the second raw material is 1:3.6 to 1:7.2;
[0026] The reduction treatment conditions of the first stage are: at 180-400° C., in a first gas atmosphere, for 4-6 hours, the copper oxide nanoparticles supported on the silicon dioxide are reduced to copper nanoparticles;
[0027] The treatment conditions of the second stage are: at 180° C. to 300° C., in a second gas atmosphere, for 20 to 150 hours, copper nanoparticles migrate to the surface of the material containing oxygen defects to form Cu atomic clusters, and obtain the copper-based catalyst.
[0028] Preferably, the first gas is a reducing gas, such as hydrogen; the second gas is a non-oxidizing gas, such as nitrogen, hydrogen or argon; the first gas flow rate is 20 to 150 mL / g material, and the second gas flow rate is 10 to 200 mL / g material.
[0029] The migration includes migration of various mechanisms, such as copper atom volatilization-deposition mechanism, or contact-transfer mechanism, etc. These migrated copper atoms are captured at the oxygen defects on the surface of the material with oxygen defects and gradually grow from single atoms to copper nanoclusters. With the continuous migration of copper atoms on the copper nanoparticles, the size of the copper nanoparticles originally loaded on the surface of silica is gradually reduced to copper nanoclusters or even copper single atoms. Therefore, in the obtained copper-based catalyst, the above copper single atoms and / or copper atom clusters are loaded on both the silica carrier and the surface of the material with oxygen defects.
[0030] In the prior art prior to the present invention, a common method for preparing single-atom catalysts is to mix a metal precursor and a reducible metal oxide carrier at high temperature, perform high-temperature treatment, and migrate metal species to the surface of cerium oxide to form single-atom species via the Ostwald ripening mechanism. However, the problem in the process of preparing copper-based catalysts using the prior art is that the copper oxide particles before migration are larger than 4nm, and copper atoms cannot be migrated at low temperatures. Therefore, in order to promote the migration of copper species on silicon dioxide, the treatment temperature during the migration process is usually 600-1000°C. The high-temperature treatment environment will cause the copper atoms that migrate to the surface oxygen-deficient substances to exceed a certain number, and the Cu single atoms will quickly agglomerate into copper nanoparticles of several nanometers or even tens of nanometers or hundreds of nanometers. Therefore, it is impossible to obtain a Cu atom cluster with a size of less than 0.8nm composed of several Cu atoms on the surface copper species.
[0031] Here, what has been ignored by all the prior art but noticed by the inventors is the difference between "copper nanoparticles" and "copper atom clusters". Although there is no strict definition recognized by the academic community, in the present invention, copper atom aggregates with a size greater than 2nm are called "copper nanoparticles", and copper atom aggregates with a size less than 0.8nm are called "copper atom clusters", and copper atom aggregates with a size between 0.8 and 2nm are called "copper sub-nanoparticles". In the copper-based catalysts reported by predecessors, the active component copper in them is in the form of "copper nanoparticles" or "copper sub-nanoparticles" without exception, and there are no reports of copper atom clusters in the form of "copper atom clusters", let alone research reports on the catalytic performance of the latter.
[0032] The present invention first prepares a material of copper oxide nanoparticles loaded with silicon dioxide as a first raw material by an ammonia evaporation method, wherein the particle size of the copper oxide nanoparticles in the first raw material is less than 4nm. Since the particle size of the copper oxide nanoparticles loaded with silicon dioxide is small, the copper oxide nanoparticles on the first raw material can be reduced to copper nanoparticles at 200-400°C and further migrate to the second raw material to form Cu single atoms and / or Cu atomic clusters composed of several Cu atoms. The lower migration temperature prevents the Cu single atoms or Cu atomic clusters from further agglomerating into copper nanoparticles, thereby obtaining the copper-based catalyst loaded with Cu atomic clusters or Cu single atoms on a mixed carrier of the present invention.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] 1. The present invention provides a method for selectively generating ethylene in an acetylene hydrogenation reaction, and specifically designs a copper-based catalyst suitable for use in the reaction. The copper-based catalyst of the present invention has a good effect on the selective hydrogenation production of intermediate product ethylene in the acetylene hydrogenation reaction. When Cu3 composed of three copper atoms is used as a catalyst, the reaction temperature is 200°C, the reaction pressure is 0.1MPa, and the feed acetylene, hydrogen, and nitrogen ratio is 1:10:89, the intermediate product ethylene yield reaches 80%, far exceeding the existing reported supported copper nanoparticle catalyst, and is equivalent to the catalytic activity of the precious metal palladium-based catalyst. The copper-based catalyst of the present invention can replace the palladium-based catalyst as an industrial catalyst. It greatly saves the catalyst production cost and reduces the energy consumption required for product separation.
[0035] 2. The present invention realizes for the first time the large-scale preparation of a copper-based catalyst whose active component is a single Cu atom and / or a Cu atomic cluster composed of several Cu atoms. The carrier of the copper-based catalyst is silicon dioxide and a substance containing surface oxygen defects, and the mass ratio of silicon oxide to the substance containing surface oxygen defects is 1:(3.6-7.2); the active component of the copper-based catalyst is a copper species, and the copper species is a single Cu atom and / or a Cu atomic cluster composed of several Cu atoms, the size of the Cu atomic cluster is less than 0.8 nm, and the loading amount of the copper species is 5%-7%.
[0036] 3. The present invention first prepares a substance of copper oxide nanoparticles loaded with silica as the first raw material by an ammonia evaporation method, wherein the particle size of the copper oxide nanoparticles in the first raw material is less than 4 nm. Since the particle size of the copper oxide nanoparticles loaded with silica is small, the copper oxide nanoparticles on the first raw material can be reduced to copper nanoparticles at 200-400° C. and further migrate to the second raw material to form Cu single atoms and / or Cu atomic clusters composed of several Cu atoms. The lower migration temperature prevents the Cu single atoms or Cu atomic clusters from further agglomerating into copper nanoparticles, thereby obtaining the copper-based catalyst of the present invention with Cu atomic clusters or Cu single atoms loaded on a mixed carrier. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The spherical aberration corrected transmission electron microscopy image of the copper-based catalyst sample 1 prepared in Example 1 and the DFT simulation image of the structure, wherein Figure a is a spherical aberration transmission electron microscopy image and a contrast signal intensity image in the S1 and S2 directions, Figure b is a local enlarged image of the box in Figure a, and Figure c is a DFT simulation image of the corresponding structure. The copper species of the copper-based catalyst sample 1 is a Cu atomic cluster (Cu3) composed of three copper atoms;
[0038] Figure 2 Figures a and b are transmission electron micrographs of the first raw material and the second raw material during the preparation process of Example 1 and Example 6, wherein Figures a and b are transmission electron micrographs of the first raw material (silicon dioxide-loaded copper oxide nanoparticles) after being reduced at 300° C. in a hydrogen atmosphere for 4 hours, and Figures c and d are transmission electron micrographs of the second raw material (cerium dioxide precursor);
[0039] Figure 3 This is a spherical aberration corrected transmission electron micrograph of the copper-based catalyst sample 2 prepared in Example 3, wherein the copper species of the copper-based catalyst sample 1 is a Cu atomic cluster (Cu 30 );
[0040] Figure 4 X-ray absorption fine structure spectra of copper-based catalyst samples 1-3 prepared in Examples 1-3 and metallic copper, cuprous oxide and cupric oxide standards, wherein A is an X-ray absorption near-edge structure spectrum, B is a derivative function diagram of the X-ray absorption near-edge structure spectrum, and C is an extended X-ray absorption fine structure spectrum;
[0041] Figure 5 The copper-based catalyst sample 1-3 prepared in Example 1-3 was used in the acetylene hydrogenation reaction, and the conversion rate of acetylene and the selectivity of ethane and ethylene were obtained. The reaction conditions were: reaction temperature 200°C, reaction pressure 0.1 MPa, acetylene: hydrogen: nitrogen ratio of 1:10:89, acetylene mass space velocity of 1300 h -1 ;
[0042] Figure 6 The copper-based catalyst sample 1-3 prepared in Example 1-3 was used in the hydrogenation reaction of dimethyl oxalate, and the conversion rate of dimethyl oxalate and the selectivity of ethylene glycol (EG) and methyl glycolate (MG) were obtained, wherein the reaction conditions were: reaction temperature 200°C, reaction pressure 2.5MPa, hydrogen-ester ratio 80, and mass space velocity of dimethyl oxalate 3h -1 ;
[0043] Figure 7 The spherical aberration corrected transmission electron microscope image and S2 direction contrast signal intensity image of the copper-based catalyst sample 4 prepared in Example 6. DETAILED DESCRIPTION
[0044] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be noted that the following examples are illustrative, not restrictive, and the scope of protection of the present invention cannot be limited by the following examples. The raw materials required in the following examples and comparative examples are all commercially available.
[0045] Example 1
[0046] Preparation of the first raw material (silicon dioxide-supported copper oxide nanoparticles):
[0047] Weigh 18g of copper nitrate trihydrate, add 100mL of deionized water, stir and dissolve, and slowly add 70mL of 28% ammonia water to make a copper ammonia solution, and stir evenly at 30°C. Then add 30% silica sol dropwise to the solution, and continue stirring and aging for 4h. Heat to 80°C to evaporate the ammonia in the solution, and monitor the pH of the solution at any time. When pH = 7, cool down and the ammonia evaporation process stops. Filter and wash the obtained mixed solution, dry it at 80°C, and calcine it at 400°C in an air atmosphere for 4h to obtain a substance of silica-loaded copper oxide nanoparticles.
[0048] Preparation of the second raw material (cerium dioxide precursor):
[0049] Weigh 25 g of cerium dioxide hexahydrate, grind it in a mortar, and calcine it at 250° C. for 2 hours in an air atmosphere to obtain a cerium dioxide precursor.
[0050] Figure 2 These are transmission electron micrographs of the first raw material and the second raw material during the preparation process of Example 1, wherein a and b are transmission electron micrographs of the first raw material (silicon dioxide-loaded copper oxide nanoparticles) after being reduced at 300°C in a hydrogen atmosphere for 4 hours, and c and d are transmission electron micrographs of the second raw material (cerium dioxide precursor).
[0051] Preparation of copper-based catalyst sample 1:
[0052] The silica-loaded copper oxide nanoparticles and cerium dioxide were mechanically mixed at a mass ratio of 1:3.6 to obtain a raw material mixture, and then the raw material mixture was subjected to online reduction treatment and heat treatment to obtain a copper-based catalyst sample 1.
[0053] Copper-based catalyst sample 1 online processing:
[0054] In this embodiment, the online treatment of the copper-based catalyst sample 1 is carried out in a fixed bed reactor. The raw material mixture that has not been heat-treated is tableted and sieved into particles of 40-60 mesh size. 0.15 mL is measured and placed in an isothermal reactor, and a hydrogen atmosphere is introduced at 300°C for reduction for 4 hours, and then the temperature is lowered to 200°C for 100 hours. The hydrogen gas flow rate is 20-150 mL / g, and the copper-based catalyst sample 1 used in the present invention is obtained.
[0055] The characterization of copper-based catalyst sample 1 is shown in Figure 1 , where Figure a is a spherical aberration transmission electron microscope image and a contrast signal intensity image in the directions of S1 and S2, Figure b is a partial enlarged image of the box in Figure a, and Figure c is a DFT simulation image of the corresponding structure. It can be seen that at this angle, the atomic spacing of Cu-Cu is 0.20nm, and the spacing of Ce-Ce is 0.31nm. Due to the low atomic number of O, it is almost invisible in the spherical aberration transmission electron microscope image. And because the atomic number of Ce is greater than that of Cu, it can be clearly found through the signal intensity in the directions of S1 and S2 that the copper species on the surface of cerium oxide exist in the form of approximately 3 Cu atomic clusters, so the copper-based catalyst sample 1 obtained in this embodiment is referred to as Cu3.
[0056] Example 2-3
[0057] In Examples 2-3, the mass percentage of copper in the silica-supported copper oxide nanoparticles was controlled to control the size of the copper species in the copper-based catalyst to prepare copper-based catalyst samples 2-3. The specific preparation conditions are shown in Table 1. The experimental conditions not shown in Table 1 are the same as those in Example 1.
[0058] Table 1 Effect of different copper nitrate addition amounts on copper species in copper-based catalysts
[0059]
[0060] The spherical aberration corrected transmission electron microscopy of the copper-based catalyst sample 3 is shown in Figure 3 .
[0061] Depend on Figure 3 It can be seen that the copper oxide nanoparticles supported on the silica were reduced to copper nanoparticles, and the copper nanoparticles successfully migrated to the cerium oxide to form a Cu atomic cluster consisting of thirty copper atoms. Therefore, the copper-based catalyst sample 3 is referred to as Cu 30.
[0062] at the same time, Figure 4 The X-ray absorption fine structure spectra of copper-based catalyst samples 1-3, where A is the X-ray absorption near edge structure spectrum (XANES), B is the derivative function diagram of the X-ray absorption near edge structure spectrum, and C is the extended X-ray absorption fine structure spectrum (EXASF), where the atomic distance of 1.85 angstroms is the peak of the Cu-O bond, and the atomic distance of 2.53 angstroms is the peak of the Cu-Cu bond. Figure 4 The XANES graph of copper in the sample can prove that the average valence state of this Cu atomic cluster is between 0 and +1; since the EXAFS graph of the Cu element only has the peak of the Cu-O bond, and no Cu-Cu bond peak appears, it can be explained that the Cu species in the catalyst of Example 2 exists in the form of a single atom; since the peak of the Cu-Cu bond in the EXAFS graph of the Cu element in the sample of Example 1 is very weak, by fitting its coordination number to 2.6, it can be explained that the copper species in Example 1 is a Cu cluster composed of 2-3 Cu atoms; since the peak of the Cu-Cu bond in the EXAFS graph of the Cu element in the sample of Example 3 is relatively weak, by fitting its coordination number to 4.8, it can be calculated that the copper species in Example 3 exists in the form of a 0.8nm Cu cluster.
[0063] Example 4
[0064] In this embodiment, the gas-phase acetylene hydrogenation reaction is carried out in a fixed bed reactor. The copper-based catalyst sample 1-3 is pressed into tablets and sieved into particles of 40-60 mesh size. 0.15 mL is measured and placed in an isothermal reactor. The reaction temperature in the reactor is controlled at 200°C. A mixed gas of 1% acetylene, 10% hydrogen and 89% nitrogen is introduced into the reaction tube. The acetylene gas hourly space velocity is 1300 h -1 , and the reaction was carried out at 0.1MPa. The product was analyzed by gas chromatography to obtain acetylene, ethylene, ethane and carbon 3-4 gas components, and the conversion rate of acetylene and the yield of ethylene and ethane were analyzed. The conversion rate of acetylene and the selectivity of ethylene and ethane are shown in Figure 5 .
[0065] from Figure 5 It can be seen that with the increase of the size of copper species in the copper-based catalyst, the selectivity of the intermediate product ethylene decreases, while the selectivity of ethane increases. When Cu3 composed of three copper atoms is used as a catalyst (copper-based catalyst sample 1) for acetylene hydrogenation reaction, the reaction temperature is 200°C, the reaction pressure is 0.1MPa, and the ratio of feed acetylene, hydrogen and nitrogen is 1:10:89, the yield of the intermediate product ethylene reaches 80%, which is far higher than the currently reported supported copper nanoparticle catalysts and is comparable to the catalytic activity of precious metal palladium-based catalysts.
[0066] Example 5
[0067] In this embodiment, the gas phase dimethyl oxalate hydrogenation reaction is carried out in a fixed bed reactor. The copper-based catalyst sample 1-3 is pressed into tablets and sieved into particles of 40-60 mesh size. 0.58 g is weighed and placed in an isothermal reactor. The reaction temperature in the reactor is controlled to 200°C. Dimethyl oxalate is gasified and mixed with hydrogen to enter the reaction tube. The hydrogen-to-ester ratio is 80, and the mass space velocity of dimethyl oxalate is 3h -1 , and the reaction was carried out at 2.5MPa. The product was analyzed by gas chromatography to obtain the components of dimethyl oxalate (DMO), ethylene glycol (EG), methyl glycolate (MG) and ethanol (EtOH), and the conversion rate of dimethyl oxalate and the selectivity of ethylene glycol (EG) and methyl glycolate (MG) were analyzed. The conversion rate of dimethyl oxalate and the selectivity of ethylene glycol (EG) and methyl glycolate (MG) are shown in Figure 6 .
[0068] from Figure 6 It can be seen that with the increase of the size of the Cu atomic cluster in the copper-based catalyst, the selectivity of the intermediate product methyl glycolate (MG) decreases, while the selectivity of ethylene glycol (EG) increases. When Cu3 composed of three copper atoms is used as a catalyst (copper-based catalyst sample 1) for the hydrogenation reaction of dimethyl oxalate, the reaction temperature is 200°C, the reaction pressure is 2.5MPa, and the feed hydrogen-ester ratio is 80, the yield of the intermediate product methyl glycolate reaches 95%, which is much higher than the currently reported copper-based catalysts and is comparable to the catalytic activity of the precious metal silver-based catalyst.
[0069] It can be seen from Example 5 that the copper-based catalyst used for the selective hydrogenation of acetylene to produce ethylene is also suitable for the selective production of the intermediate product methyl glycolate in the hydrogenation reaction of dimethyl oxalate. In other words, the copper-based catalyst has a good effect on the selective production of intermediate products in the chain hydrogenation reaction of acetylene and dimethyl oxalate.
[0070] Example 6
[0071] This example is the preparation of copper-based catalyst sample 4:
[0072] The preparation method of the first raw material and the second raw material is the same as that in Example 1, and then the first raw material is subjected to a first-stage reduction treatment, and then mixed with the second raw material, and then subjected to a second-stage reduction treatment after mixing to obtain the copper-based catalyst sample 4, specifically: the first raw material is first placed in an isothermal reactor, introduced into a hydrogen atmosphere and reduced at 300°C for 4 hours, and then mixed with the second raw material, and after mixing, maintained at 200°C for 100 hours in a nitrogen atmosphere; the hydrogen gas flow rate in the first stage is 20-150 mL / g, and the nitrogen gas flow rate in the second stage is 10-200 mL / g.
[0073] Spherical aberration corrected transmission electron microscopy of copper-based catalyst sample 4 Figure 7 It can be seen that compared with the copper-based catalyst sample 1 Figure 1 Similarly, the copper oxide nanoparticles supported on the silicon dioxide are reduced to copper nanoparticles, and the copper nanoparticles successfully migrate to the cerium oxide to form a Cu atomic cluster composed of three copper atoms. Therefore, the preparation method can also obtain the copper-based catalyst described in the present invention, in which the copper species is a Cu atomic cluster composed of several Cu atoms.
[0074] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A method for improving the selectivity of hydrogenation reaction to generate intermediate products, characterized in that: The selective hydrogenation reaction is a reaction of selectively hydrogenating acetylene to generate ethylene. The catalyst used is a copper-based catalyst loaded with Cu atom clusters and / or Cu single atoms on a mixed carrier. The copper-based catalyst includes a carrier and an active component. The carrier is silicon dioxide and a substance containing oxygen defects on the surface. The mass ratio of silicon dioxide to the substance containing oxygen defects on the surface is 1:(3.6-7.2); the active component is a copper species, and the copper species is a Cu single atom and / or a Cu atom cluster composed of several Cu atoms. The size of the Cu atom cluster is less than 0.8 nm, and the number of Cu atoms in the Cu atom cluster is less than 30. Based on the total mass of the copper-based catalyst, the loading amount of the copper species is 5%-7%; The preparation method of the copper-based catalyst comprises the following steps: (1) providing a material of silicon dioxide loaded copper oxide nanoparticles as a first raw material, wherein the particle size of the copper oxide nanoparticles is less than 4 nm; (2) Providing a substance with surface oxygen defects as a second raw material; (3) mixing the second raw material with the first raw material, and performing the first stage reduction treatment and the second stage treatment after the mixing; or, The first raw material is first subjected to a first stage reduction treatment, and then mixed with the second raw material, and then subjected to a second stage treatment after mixing; The mass ratio of the first raw material to the second raw material is 1:3.6 to 1:7.2; The reduction treatment conditions of the first stage are: at 180-400° C., in a first gas atmosphere, for 4-6 hours, the first gas is a reducing gas selected from hydrogen, and the first gas flow rate is 20-150 mL / g material; The treatment conditions of the second stage are: at 180° C. to 300° C., in a second gas atmosphere, for 20 to 150 hours, the second gas is a non-oxidizing gas selected from nitrogen, hydrogen or argon, and the second gas flow rate is 10 to 200 mL / g material; The copper-based catalyst is obtained after the reduction treatment in the first stage and the treatment in the second stage.
2. The method according to claim 1, characterized in that Acetylene is mixed with hydrogen and nitrogen and then fed into the reactor for selective hydrogenation reaction. The mass space velocity of acetylene is 800-1300 h -1 The ratio of acetylene, hydrogen and nitrogen is 1:10:89, the reaction temperature in the reactor is 80~240℃, and the reaction pressure is normal pressure~0.1 MPa.
3. The method according to claim 1, characterized in that The substance containing oxygen defects on the surface is a metal oxide containing oxygen defects on the surface, and the metal oxide containing oxygen defects on the surface is selected from cerium oxide, zinc oxide, zirconium oxide, titanium oxide or manganese oxide; the silicon dioxide has a layered structure, and the particle size of the substance containing oxygen defects on the surface is 4.0nm~20.0nm; the average valence of copper in the copper species is 0~1.
4. The method according to claim 1, characterized in that: The mass percentage of copper in the silica-loaded copper oxide nanoparticles in step (1) is 5% to 50%. The preparation method of the silica-loaded copper oxide nanoparticles comprises the following steps: (11) dissolving copper nitrate trihydrate in water, then adding ammonia water, stirring and mixing to obtain a first mixed solution; (12) adding silica sol dropwise to the first mixed solution, stirring, and then removing ammonia components in the first mixed solution by distillation to obtain a second mixed solution; (13) Filter the second mixed solution obtained in step (12), collect the filter cake, wash it, and calcine it in an air atmosphere to obtain a material of silica-loaded copper oxide nanoparticles.
5. The method according to claim 4, characterized in that The concentration of aqueous ammonia in step (11) is 20% to 28%; the volume ratio of aqueous ammonia to water is 1:1.12 to 1:2.31; the distillation temperature in step (12) is 60° C. to 90° C., and the pH of the solution after distilling away the ammonia component in the first mixed solution is 6.5 to 8.
5.
6. The method according to claim 1, characterized in that In step (2), the mass ratio of the first raw material to the second raw material is 1:1.14 to 1:5.62.